Influence of self-reported concussion history and a dual-task paradigm on multidirectional gait and cognitive performance of athletes - Talarico, M. K.; Brancaleone, M. P.; Berezne, K. E.; Onate, J. A.; Boucher, L. C. (International Journal of Athletic Therapy & Training, 2022)
Single-task assessments may not identify lingering effects following a concussion that may be detected under dual-task (DT) paradigms. The purpose of this study was to determine the effects of a novel DT paradigm and concussion history on gait and cognitive performance. Hockey and rugby club college athletes (n = 26) completed a box drill and the color and word Stroop test under single task and DT. Distance ambulated around the box, response rate, and accuracy were recorded to calculate dual-task cost. Mean comparisons and linear mixed-effects regression models were performed. Compared to athletes with no concussion history, those with a history had a greater motor than cognitive dual-task cost and were 3.15% less accurate in Stroop responses (p < .01). Athletes walked 0.72-m shorter distance under DT compared to single task (p = .04). A multidirectional, low-tech DT assessment may highlight long-term motor and cognitive deficits among athletes with a concussion history, which will provide valuable information to prepare and track performance within an athletic season.